Significance of Audit Committee Roles in India: A Study of Auditors’ Perception Using Analytic Hierarchy Process - Mamta Mishra; Amarjeet Kaur Malhotra (STIE Malangkucecwara, 2016)
The need for strong governance mechanisms has become increasingly louder after the spate of corporate accounting frauds over the last few decades. In India, the Satyam fiasco tarnished the reputation of the audit profession and underlined the need for overhauling the corporate governance framework. The Companies Act, 2013 ushered in a new era of corporate governance in India, with enhanced focus on audit committees. The present study aims to examine the significance of board audit committee roles from the perspective of auditors. Analytic Hierarchy Process (AHP) is used to analyze the responses collected from 50 auditors, wherein the auditors were asked to assign ranks to various audit committee roles through paired comparison method. The AHP analysis shows that as per auditors’ perception, the most significant responsibility of audit committee is to monitor auditor independence and performance, and review the effectiveness of the audit process. There is an implied acknowledgement that the audit process is not free from managerial intervention. The research findings could guide regulators and lawmakers to empower audit committees with more definitive authority over the company’s financial reporting process. Audit committees, though a part of the board, need to be perceived as a neutral body by both the company and auditors. Considering the pool of available talent in India, a 100% independent audit committee might emerge as a feasible answer for neutrality.